Database systems for advanced applications : 18th International Conference, DASFAA 2013, International Workshops: BDMA, SNSM, SeCoP, Wuhan, China, April 22-25, 2013. Proceedings - Meng, Xiaofeng; Chen, Lei; Winiwarter, Werner; Song, Wei; Hong, Bonghee (Lecture Notes in Computer Science, 2013)
This book constitutes the workshop proceedings of the 18th International Conference on Database Systems for Advanced Applications, DASFAA 2013, held in Wuhan, China, in April 2013.  The volume contains three workshops, each focusing on specific area that contributes to the main themes of the DASFAA conference: The First International Workshop on Big Data Management and Analytics (BDMA 2013), the Third International Workshop on Social Networks and Social Web (SNSM 2013) and the International Workshop on Semantic Computing and Personalization (SeCoP 2013).